Effect of radiation-induced vacancy saturation on the first-order phase transformation in nanoparticles: insights from a model - Aram Shirinyan; Yuriy Bilogorodskyy (Beilstein Journal of Nanotechnology)
By employing a model of nanomaterials with polymorphic phase transitions and using a thermodynamic approach to describe the effects of vacancy saturation, irradiation dose, powder dispersion, and surface energies, we demonstrate the possibility of radiation-induced phase transitions and the zones of radiation stability for nanoparticles. We utilize nanoparticles exhibiting transitions from the body-centered cubic α phase to the face-centered cubic β phase, and the reverse transition from β phase to α phase, as a model system for first-order phase transformations. We incorporate nucleation through the appearance and growth of the nucleus of a new phase, resulting in the formation of a two-phase α+β system, and we highlight the importance of accounting for nucleation. Our model study reveals that very small α-phase particles are unstable (while very small β-phase particles are stable) because of surface effects. There is an intermediate zone of sizes and parameters where radiation-induced defects become important so that the α-phase particle is unstable without irradiation but becomes stable under irradiation. For large sizes and low temperatures, the α→β transformation cannot occur regardless of irradiation because of bulk driving forces; initially, α-phase particles are stable, whereas the β-phase particles are unstable. In some cases, nucleation requires a large additional energy change, resulting in a low probability of phase change fluctuations. This behavior is confirmed by calculations for iron particles under irradiation. Substances characterized by high vacancy migration energy, small diffusion coefficients of defects, and low temperatures of first-order phase transitions can serve as suitable candidates for radiation-induced phase transitions in nanosystems. Ceramic nanomaterials, which possess high vacancy migration energy, will have their behavior significantly influenced by radiation doses. In contrast, most metals exhibit small vacancy migration energy and demonstrate better resistance to irradiation, making them recommended candidates for nuclear materials.